2022
DOI: 10.1111/nbu.12551
|View full text |Cite
|
Sign up to set email alerts
|

Do ancient wheats contain less gluten than modern bread wheat, in favour of better health?

Abstract: Popular media messaging has led to increased public perception that gluten‐containing foods are bad for health. In parallel, ‘ancient grains’ have been promoted with claims that they contain less gluten. There appears to be no clear definition of ‘ancient grains’ but the term usually includes einkorn, emmer, spelt and Khorasan wheat. Gluten is present in all wheat grains and all can induce coeliac disease (CD) in genetically susceptible individuals. Analyses of ‘ancient’ and ‘modern’ wheats show that the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…In some cases, this renaissance has been associated with the supposed miraculous properties of these old crops. In general, such statements are not supported by any scientific basis and both the nutritional and nutraceutical properties of ancient wheats have been shown to be very similar to those of modern wheat [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. However, other real benefits, such as the expansion of diversity in food, are little appreciated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, this renaissance has been associated with the supposed miraculous properties of these old crops. In general, such statements are not supported by any scientific basis and both the nutritional and nutraceutical properties of ancient wheats have been shown to be very similar to those of modern wheat [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. However, other real benefits, such as the expansion of diversity in food, are little appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, this renewed interest has resulted in the development of numerous studies on these species, comparing their characteristics with the ones of modern wheat [ 50 , 51 ]. However, many of these studies have been carried out with a limited number of genotypes [ 37 ], which could create bias in the results and undervalue the true role of these old materials.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the high-yielding modern varieties have a lower protein content and decreased proportions of gliadins but an increase in glutenins. , The gliadin/glutenin proportion similarly varies by wheat species: while glutenin is the dominant fraction in common wheat, gliadin makes up the highest fraction in species of so-called ancient wheats (einkorn, emmer, and spelt) as well as having an overall higher protein content. , Environmental conditions such as soil, temperature, and irrigation also play a role in protein composition . In parallel to a decrease in overall protein content in modern bread wheat, the starch content has increased . In the past, a pure starch paste might, therefore, have been challenging to achieve, based on a lower starch content and imperfect techniques to separate starch from flour, resulting in a starch paste containing a higher protein content.…”
Section: Discussionmentioning
confidence: 99%
“… 104 In parallel to a decrease in overall protein content in modern bread wheat, the starch content has increased. 105 In the past, a pure starch paste might, therefore, have been challenging to achieve, based on a lower starch content and imperfect techniques to separate starch from flour, resulting in a starch paste containing a higher protein content. Our analyses here show that, even in commercial starch, a significant amount of proteins, including some gluten, is found.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, plant breeding of wheat might have contributed to a decrease in the nutritional quality, e.g., minerals and phytochemicals, of the wheat, and breeding toward improved bread-making quality may have resulted in an increase in components having a negative effect on human health (allergy, coeliac disease, non-coeliac gluten sensitivity, irritable bowel syndrome) (23). However, recent studies (24,25) have found no evidence of a lower quality of modern wheat for human health as compared to ancient wheat genotypes. Instead, some studies have indicated the modern processing methods of wheat as a risk factor of their health impact (26).…”
Section: Introductionmentioning
confidence: 99%